ANALISIS PERTUMBUHAN EKONOMI DAN PENYERAPAN TENAGA KERJA DI PROVINSI JAWA TENGAH - Nurrohman, Riyadi; Arifin, Zainal (Jurnal Ekonomi Pembangunan, 2010)
This study aims to determine the pattern of economic growth and employment potential in districts of Central Java Province the period 2005 - 2009, and the causality between economic growth and employment in the province of Central Java. The analysis used in this study is analysis of economic growth, typology, ILOR Klassen (Labour Incremental Output Ratio), and granger causality test. The results of this study indicate that the economic growth that occurred in 2005-2009 with an average value of the highest economic growth> 4.45 in eight districts, or 22.85% of the total districts / cities in Central Java province. Average value of the highest economic growth between 3.08 to 3.35 as much as 15 districts, or 42.85%. While the average value of the lowest economic growth <2.61 only one district or 2.85% of the entire district. Employment in the province of Central Java with a big potential categories found as many as five districts / cities, the category of potentially as many as 26 districts, while the categories are not potentially as many as four counties. From the Granger Causality test result yielded that the relationship between them is one way that employment cause/affect economic growth.